An Electrochemical Study of PCl3 and POCl3 in the Room Temperature Ionic Liquid [C4mpyrr][N(Tf)2] - Silvester, Debbie; Aldous, L.; Lagunas, M.; Hardacre, C.; Compton, R. (American Chemical Society, 2006)
Voltammetric studies of PCl3 and POCl3 have not been reported in the literature to date, probably due to the instability of these molecules in conventional aprotic solvents giving unstable and irreproducible results. From a previous study [Amigues et al. Chem. Commun. 2005, 1-4], it was found that ionic liquids have the ability to offer a uniquely stable solution phase environment for the study of these phosphorus compounds. Consequently, the electrochemistry of PCl3 and POCl3 has been studied by cyclic voltammetry on a gold microelectrode in the ionic liquid [C4mpyrr][N(Tf)2] (1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide). For both compounds, reduction and oxidation waves were observed and a tentative assignment of the waves is given. For PCl3, the reduction was thought to proceed via the following mechanism: PCl3 + e- h PCl3 -, PCl3 - h Cl- + P¥Cl2, and Cl- + PCl3 h PCl4 -. For POCl3, the suggested reduction mechanism was analogous to that of PCl3: POCl3 + e- h POCl3 -, POCl3 - h Cl- + P¥OCl2, and Cl- + POCl3 h POCl4 -. In both cases P¥Cl2 and P¥OCl2 are likely to engage in further reactions. Potential step microdisk chronoamperometry was carried out on the reductive waves of PCl3 and POCl3 to measure diffusion coefficients and number of electrons transferred. It was found that the diffusion of PCl3 was unusually slow (3.1 10-12 m2 s-1): approximately 1 order of magnitude less than that for POCl3 (2.2 10-11 m2 s-1). For both PCl3 and POCl3, a “split wave” was observed, with an overall electron count of 1. This observation is shown to be consistent with and to “fingerprint” the mechanisms proposed above.